Quality Management of Academic Supervision in Indonesian Madrasahs: A Case Study Analysis of Principal Leadership and Teacher Professional Development - Burhan, Barri Mochamad; Sauri, Supyan (Papanda Publisher, 2025)
The quality of education in madrasahs faces significant challenges, particularly regarding systematic academic supervision and teacher professional competence development. This study examined the implementation of quality management principles in academic supervision conducted by madrasah principals and its impact on enhancing teacher professionalism competence. A qualitative case study approach was employed at Madrasah Aliyah Cijawura, Bandung City, Indonesia. Data were collected through in-depth interviews with madrasah principals, teachers, and supervisors, direct observations of supervision activities, and document analysis. Thematic analysis was conducted using Deming's quality management framework encompassing planning, implementation, evaluation, and follow-up dimensions. The findings revealed four critical dimensions of effective supervision quality management: comprehensive planning incorporating stakeholder needs assessment, structured implementation through classroom observation and collaborative feedback, multi-dimensional evaluation with diverse stakeholder perspectives, and sustained follow-up activities ensuring continuous professional growth. Teachers demonstrated measurable improvements in pedagogical competence, subject mastery, classroom management, and professional confidence following systematic supervision interventions. The successful application of Deming's Plan-Do-Check-Act framework demonstrates the adaptability of quality management principles in Islamic educational contexts. The systematic supervision approach addresses supervisor identity formation challenges while creating conditions for collaborative professional development aligned with social constructivist principles.